2022
DOI: 10.3390/ma15082908
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort and Electrostatic Properties of Socks Containing Fibers with Bio-Ceramic, Silver and Carbon Additives

Abstract: Socks are an important part of our clothing used in everyday activities. In order to ensure thermal comfort during wear in cool outdoor or indoor conditions, and for health improvement, socks must have effective thermoregulation properties. Chemical far-infrared (FIR) fibers with different bio-ceramic compounds incorporated into socks’ structures can provide an improved thermoregulation effect to the wearer of the socks. Fibers with silver and carbon additives incorporated in their structures can also affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The thermal resistance of socks has been measured under steady state conditions using the thermal foot model [ 3 , 16 , 36 ] and the sock-shaped hot plate [ 22 , 23 ]. The thermal resistance of the sock fabrics was measured by a standardized method according to EN ISO 11092:2014 using a sweating guarded hot plate [ 2 , 30 , 37 ]. Since this test requires rectangular seamless samples measuring 510 × 510 mm, the thermal resistance of the sock fabrics was also measured on the smaller knit samples using the Permetest or Alambeta tester (equivalent to ISO 8301:1991) [ 16 , 21 ] and calculated as the quotient of the fabric thickness and thermal conductivity parameters of the sample [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal resistance of socks has been measured under steady state conditions using the thermal foot model [ 3 , 16 , 36 ] and the sock-shaped hot plate [ 22 , 23 ]. The thermal resistance of the sock fabrics was measured by a standardized method according to EN ISO 11092:2014 using a sweating guarded hot plate [ 2 , 30 , 37 ]. Since this test requires rectangular seamless samples measuring 510 × 510 mm, the thermal resistance of the sock fabrics was also measured on the smaller knit samples using the Permetest or Alambeta tester (equivalent to ISO 8301:1991) [ 16 , 21 ] and calculated as the quotient of the fabric thickness and thermal conductivity parameters of the sample [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the abrasion resistance of socks knitted in a single jersey structure can be increased by a number of measures: the use of yarns with a higher linear density, yarns with a higher twist coefficient and folded yarns, the addition of polyester fibers in blends and the addition of elastic yarns (polyamide or elastane filaments) to the structure [ 4 , 15 , 33 ]. In recent research, highly functional socks were knitted in the plain single jersey pattern in full plating using three-ply and two-ply twisted yarns composed of various high-performance fibers with PCMs, insect repellent, bio-ceramic, silver and carbon additives [ 2 , 37 ]. The use of spiral auxiliary yarns consisting of various combinations of high-performance para-aramid, elastomeric, polyamide, polyester and conventional cotton fibers has also been investigated for the development of abrasion-resistant socks [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Socks are the clothes put on feet to attain needed comfort and performance attributes. [3][4][5][6] Knitting technology is the most preferred technique for socks engineering. Knitting has surpassed weaving as the most widely regarded textile manufacturing process due to its simplicity and comfort characteristics.…”
Section: Introductionmentioning
confidence: 99%